DETECTION OF STX2 COLIPHAGES IN STRAIN OF ESCHERICHIA COLI ISOLATED FROM BOVINE FLEECE AND MILK FILTERS - G. Delle Donne; R. Mancusi; M. Trevisani (Italian Journal of Food Safety, 2011)
Lambda(4)-phage vectors of gene codifying for synthesis of Shiga-toxins are suspected to be involved in the virulence evolution of Vero-Toxin producing Escherichia coli(VTEC). Herds of domestic or wild ruminants are reservoirs of these bacteria, but excretion with faeces is more frequent in groups of heifers and feeder calves. Studies have shown that slurries produced by infected herds are often positive for VTEC and that Stx2 carrying lambda coliphages can be isolated. These viruses can induce lysogenic cycles only in some strain of Escherichia coli and the Stx gene is then integrated in the bacterial chromosome. When these bacteria also posses other virulence traits, like those responsible for the intimate attachment to the enteric mucosal cells (eae or saa) the recombinant strains might became pathogen for humans. Our research was aimed at detecting the coliphages form ten Stx2 positive strains isolated in our previous studies. We have included strains, possessing or not the ‘eae’ genes. In addition we have used other isolates originating from slaughterhouses, with the aim of evaluating their susceptibility to the isolated 4-phages. Following induction of a lytic cycle with mitomycin C, the strains were screened by hybridization of plaque blots with Stx2 probes. The purified extracts of eight of the ten strains produced plaque/halos of lysis in cultures of susceptible strains, thus showing these strains were infected by inducible phages, but only one proved to be Stx2 carrier. Attempt to obtain new lysogens using the purified Stx2 phage with other strains ‘eae’ positive and STx negative isolated from slaughterhouses were unsuccessful. Stx2 lysogens were obtained only using the reference strains DM1187.